The Impact of Disease Comorbidities in Alzheimer's Disease - Santiago, Jose A.; Potashkin, Judith A. (Frontiers in Aging Neuroscience, 2021)
A wide range of comorbid diseases is associated with Alzheimer's disease (AD), the most common neurodegenerative disease worldwide. Evidence from clinical and molecular studies suggest that chronic diseases, including diabetes, cardiovascular disease, depression, and inflammatory bowel disease, may be associated with an increased risk of AD in different populations. Disruption in several shared biological pathways has been proposed as the underlying mechanism for the association between AD and these comorbidities. Notably, inflammation is a common dysregulated pathway shared by most of the comorbidities associated with AD. Some drugs commonly prescribed to patients with diabetes and cardiovascular disease have shown promising results in AD patients. Systems-based biology studies have identified common genetic factors and dysregulated pathways that may explain the relationship of comorbid disorders in AD. Nonetheless, the precise mechanisms for the occurrence of disease comorbidities in AD are not entirely understood. Here, we discuss the impact of the most common comorbidities in the clinical management of AD patients.